Jerzy Kmita’s methodological interpretation of Karl Marx’s philosophy. From ideology to methodological concepts - Pałubicka, Anna (Hybris, 2017)
The article presents J. Kmita’s methodological interpretation of selected cognitive methods used by K. Marx. Those methods were (and I believe they still are) significant for the social sciences and the humanities, even a century after they had been developed. J Kmita’s interpretation reveals specificity of epistemic procedures carried out by the author of “Capital” and emphasizes contemporary actuality of Marx’s epistemological ideas. To achieve that aim, Kmita refers to the concepts established in the field of philosophy of science of his time. According to J. Kmita, the attractiveness of Marx’s approach lies in the opportunity to develop a methodological interpretation of Marx philosophy, which in turn enables the formation of a unique theory of science development, alternative to those provided by logical positivism, falsificationism, neopragmatism or sociology of knowledge. Such theory would combine the perspective of sociology of knowledge with an epistemological approach to the development of science.